The Potential of Using the Early Eocene-Oligocene Coal’s Formation in Tanjung Barito Basin - Tanggara, Deddy NSP (Interdisciplinary Social Studies, 2022)
Research on the development of coal utilization for Indonesia is very important considering that Indonesia is a country that has large amounts of coal reserves, so it can use its coal not only as a source of energy for power plants but also needs to incentivize coal conversion for increased added value. To analyze the potential of using the early Eocene-Oligocene coal's formation in Tanjung Barito basin. In this study, data sources derived from laboratory test results will be analyzed by descriptive methods with quantitative approaches.  The results of this study were obtained through proximate tests on coal samples TIAN-0 1 and TIAN-0 2 total value moisture of 9.1 4% weight as-received basis (arb) and Moisture in the Analysis sample worth 3.67%, value ash content 7.35%, flying substance value 36.11%, tethered carbon value 52.86% with air-dried base (ADB) basis % weight and total sulfur value 0.36% with air-dried base (ADB) % weight. Based on the gross calorific value with an average caloric value of 7353 Kcal/kg, sample coal is classified as high volatile coal A bituminous. The results of testing on the potential of sample coal caking also indicate the potential utilization of Early Eocene-Oligocene coal Tanjung Formation to be used in the metallurgical industry with the results of testing the value of the Free Swelling Index sample showing the swelling ability of the coal with a value of 6 and 2.5 and G indexes 66 and 92.